A Look at the History of Darband - Safarova Sanobar (Journal of Research in Innovative Teaching and Inclusive Learning, 2024)
One of the main tasks of historiography today is to cover the many thousand-year history of our people in an objective manner based on the ideas of national independence. The images of Zarautsoy, located in the oasis, were created based on the thinking and imagination of primitive people, while Darband is considered to be the priceless abode of our ancestors who lived in a settled manner. The initial urban planning culture formed in Zharkoton is a prelude to the processes of urbanization development in our country. The early days of Uzbek statehood are closely related to the ancient Bactrian regions that settled on this land. The oasis was a shield even in the times when the enemy attacked the territory of our country from the south.